Strategi dan Model Bisnis Usaha Kuliner Pascapandemi: Studi Kasus Rumah Makan XYZ - Widia Citra Anggundari; Arif Imam Suroso; Budi Setiawan (Jurnal Aplikasi Bisnis dan Manajemen, 2023)
XYZ restaurant is a restaurant that serves the main menu of rice and chicken soup. In carrying out its business activities, XYZ restaurant faces various obstacles, such as the trend of a significant decline in turnover. Restaurant owners are forced to evaluate their business activities in light of the current conditions, namely the new normal. This study aims to design a business strategy and formulate a new business model for XYZ restaurant. The research was conducted using qualitative methods. The type of data collected consists of primary and secondary data, with data collection methods carried out through interviews, questionnaires, and literature studies. The approach is carried out through analysis of the business model canvas, analysis of internal and external environmental factors, the IE matrix, and the SWOT matrix. The results of this research are strategies that can be implemented by XYZ restaurants and the results of formulating a new business model for XYZ restaurants. The strategies that can be implemented are building effective relationships and communication with customers, optimizing the use of digital marketing, adding a variety of food and beverage menus, improving product and service quality, seeking and adding collaboration partners, clarifying employee SOPs, and improving the quality of human resources. In the new business model, there are nine elements added to the business model canvas. The XYZ restaurant is deemed to need to implement a strategy and make improvements to its business model so that it can survive amidst high competition in the culinary industry in Bogor City. Keywords: business model canvas, restaurant, strategy, SWOT analysis, culinary